Changes in the expression of genes that regulate apoptosis as a factor in the development of chemoresistance in soft tissue sarcoma - T. I. Fetisov; S. A. Khazanova; P. A. Shtompel; E. S. Trapeznikova; A. A. Tararykova; V. Yu. Zinovyeva; V. I. Marshall; A. A. Lowenger; I. S. Kupaeva; D. V. Rogozhin; A. Yu. Bokhyan; G. A. Belitsky; et al. (Успехи молекулярной онкологии)
Introduction. The active use of highly toxic chemotherapy in the treatment of soft tissue sarcomas determines the need to search for criteria and markers of chemoresistance of patients to the therapy.Aim. To study the connection between tumor cell resistance to chemotherapy and expression levels of apoptosis-regulating proteins (PUMA, PMAIP-1, PIDD-1, AIFM-2, Bax, GADD45a) in primary cultures of soft tissue sarcomas.Materials and methods. Primary cultures of soft tissue sarcomas were obtained using enzymatic digestion, cell death was evaluated using resazurine assay. Gene expression was measured using real-time polymerase chain reaction, protein levels using immunoblotting assay.Results. 73 primary cultures of soft tissue sarcomas were obtained, for which chemosensitivity to doxorubicin, ifosfamide, docetaxel, gemcitabine, pazopanib and their combinations was determined using a resazurin cytotoxicity test. Associations of AIFM-2 gene expression with resistance to pazopanib, doxorubicin and its combination with ifosfamide were found in liposarcoma, synovial and undifferentiated pleomorphic sarcomas. In addition, associations between the expression of the Bax, PUMA, PMAIP-1, GADD45a and PIDD-1 genes and resistance to the studied drugs in various nosological subgroups of sarcomas were identified. When studying the amount of protein, it was revealed that undifferentiated pleomorphic and synovial sarcomas with a low content of GADD45a are more resistant to the studied drugs. Liposarcomas with high Bax expression are more resistant to docetaxel and gemcitabine, while synovial sarcomas with high Bax expression are more sensitive to doxorubicin and ifosfamide.Conclusion. The data obtained indicate a relationship between the activity of the studied genes-regulators of apoptosis and resistance to drugs used in the treatment of soft tissue sarcomas.